Phylogenetic analysis of ornamental Pomacentridae from the southern coast of West Java - Munatul Khayah Almusyarofah; Romanus Edy Prabowo; Agus Nuryanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
Abstract. Pomacentridae has a wide distribution in Indonesia waters. Research on species richness of Pomacentridae has been carried out in some areas in Indonesia. However, there are no data about the relationships of Pomacentridae on the southern coast of West Java. This research aims to know the evolutionary kinship of Pomacentridae ornamental fish in Ujung Genteng and Taman Manalusu Beach, West Java. This research used a survey method with a judgment sampling technique. The parameters measured were the consistency index (CI) and character evolution of the resulting phylogenetic tree. Cladogram reconstructed based on maximum parsimony algorithm with 1000 bootstrap replicates in PAUP software. The result showed that the tree had a CI value of 0.6000 which indicated low homoplasy. Pomacentridae formed a monophyletic group when they compared with Chaetodon collare as outgroup. The Pomacentridae clade divided into two subclades. The first subclade consisted of Abudefduf indicus as a basal species, then Neoglypydodon bonang and Plectroglyphidodon lacrymatus have a closed kinship and diverged after Dascyllus trimaculatus, and then Abudefduf notatus and Abudefduf sexfaciatus have a close kinship and diverged after Abudefduf vaigiensis. The second subclade referred to as a basal group, and within this subclade, Chrysiptera brownriggii has a closely related to Chrysiptera unimaculata and diverged after Chromis opercularis.Keywords: Cladistics, damselfish, meristic, morphometric, Pomacentridae